2015
DOI: 10.1016/j.molimm.2014.10.023
|View full text |Cite
|
Sign up to set email alerts
|

The immunology of the porcine skin and its value as a model for human skin

Abstract: The porcine skin has striking similarities to the human skin in terms of general structure, thickness, hair follicle content, pigmentation, collagen and lipid composition. This has been the basis for numerous studies using the pig as a model for wound healing, transdermal delivery, dermal toxicology, radiation and UVB effects. Considering that the skin also represents an immune organ of utmost importance for health, immune cells present in the skin of the pig will be reviewed. The focus of this review is on de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
276
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 399 publications
(285 citation statements)
references
References 73 publications
7
276
0
2
Order By: Relevance
“…Porcine skin is an excellent model for biomedical research because of its anatomical, histological, immunological, immunohistochemical, and genomic similarities to human skin. We have also previously shown that human and porcine skin susceptibility to UV radiation is comparable .…”
Section: Introductionmentioning
confidence: 99%
“…Porcine skin is an excellent model for biomedical research because of its anatomical, histological, immunological, immunohistochemical, and genomic similarities to human skin. We have also previously shown that human and porcine skin susceptibility to UV radiation is comparable .…”
Section: Introductionmentioning
confidence: 99%
“…The maximum distance detectable by NIR through porcine skin, used as a human skin analog ( Figure 3G), was 12 mm. 26 Figure 3H presents an ultrasound recording of normal human carotid artery bifurcation annotated for the ICA, ECA, and CCA. The linear dashed bar in Figure 3H indicates 11.89 mm depth of the human carotid artery bifurcation from the vertical distance from the neck surface (courtesy of Dr Aaron O Shiloh).…”
mentioning
confidence: 99%
“…This applies to its general structure, thickness, hair follicle content, pigmentation, collagen and lipid composition. 8 Porcine epidermal thickness, for example, has been shown to approximate human epidermis, and range from 30 to 140 mm, which is comparable to human skin thickness of 50-120 mm. 8 It is thus optimal to use porcine skin-containing VCA as a platform for establishing pathologic components for scoring systems.…”
Section: Discussionmentioning
confidence: 86%